Novel Targets and Interventions for Cognitive Complications of Diabetes - Wolf, Victoria; Abdul, Yasir; Ergul, Adviye (Frontiers in Physiology, 2022)
Diabetes and cognitive dysfunction, ranging from mild cognitive impairment to dementia, often coexist in individuals over 65 years of age. Vascular contributions to cognitive impairment/dementia (VCID) are the second leading cause of dementias under the umbrella of Alzheimer’s disease and related dementias (ADRD). Over half of dementia patients have VCID either as a single pathology or a mixed dementia with AD. While the prevalence of type 2 diabetes in individuals with dementia can be as high as 39% and diabetes increases the risk of cerebrovascular disease and stroke, VCID remains to be one of the less understood and less studied complications of diabetes. We have identified cerebrovascular dysfunction and compromised endothelial integrity leading to decreased cerebral blood flow and iron deposition into the brain, respectively, as targets for intervention for the prevention of VCID in diabetes. This review will focus on targeted therapies that improve endothelial function or remove iron without systemic effects, such as agents delivered intranasally, that may result in actionable and disease-modifying novel treatments in the high-risk diabetic population.